System Of Payment Of Tax Obligations (SPOT) Related To The Payment Capacity Of Construction Companies In Peru - Grijalva Salazar, Rosario Violeta (2020)
Objective: To establish that the detection system affects the ability to pay in construction companies, period 2017. Method: It is an explanatory, quantitative, transversal, retrospective, correlational and non-experimental substantive type research, based on measurement, numerical evaluation and statistical analysis. Results: The sample consisted of 20 applications, to which the Cronbach's Alpha tests were applied, and then the variables will be related; the results that have been obtained after having performed all the evaluation procedures, execution in the payment system of tax obligations (SPOT) are that it does affect the short-term liquidity in the construction companies. The population consists of 50 workers of the construction companies in the district of San Miguel, according to the 95% confidence level, the sample will be 44. Conclusions: In order to measure the results, the regression method has been used; a correlation of 0.899 has been found, that is, being greater than 0.05, gives the validity of the hypothesis proposed by the authors.